Framing of disease risk messages in airport banners - Ting, Su Hie; Collin, Anak Jerome (Global Academic Excellence (GAE), 2017)
Communication of disease risk aims to persuade the public to take health preventive measures. The receptivity of the public depends on their knowledge of the disease. However, health risk messages can be framed to heighten awareness of the disease threat. This study examined the framing and persuasiveness of disease risk messages in airport banners produced by the Ministry of Health Malaysia. The banners for Zika, Hand, Foot and Mouth Disease, Ebola Virus Disease, malaria, and Middle East Respiratory Syndrome-Coronavirus Disease were analysed to find out: (1) the messages on severity, susceptibility and cues to action found in airport banners, and (2) appeals to logos, pathos and ethos were used to persuade the public to take health preventive measures. The results showed that the banners are very informative on risk groups, disease symptoms, and recommended actions. However, the logos focus of the messages may not construct the diseases as a public health threat because a restricted group of airline passengers are identified as susceptible to the diseases and symptoms presented are mild. The study showed that pathos or emotional appeal is lacking in the airport banners and this should be considered to increase the persuasiveness of the disease risk communication.